(3EOGQI GdNOeGJ GdSjGMjI (B/s - (3CHh ZRGdI, UaGAs ((3YeGf(B: s (3OGQ RgQGf ddfTQ hGdJhRjY(B, s, 2006)
(3SeGJ GdNOeI GdSjGMjI hEOGQI GdLhOI GdTGedI ddNOeI GdSjGMjI, JSYjQ GdNOeGJ GdSjGMjI, JhRjY GdNOeGJ GdSjGMjIs
Keywords: (3GdNOeI GdELJeGYjIs; (3GdSjGMIs; (3VHW GdLhOI(B- (3GdSjGMIs